Behavioral and Clinical Correlates of Frequent Self-Reported Sleep Bruxism Among Thai Participants: A Cross-Sectional Study - Kanyawee Teepun; Nichakan Polpetch; Teetat Srikaue; Pongkit Ekvitayavetchanukul (American Journal of Physical Education and Health Science, 2026)
Sleep bruxism is a sleep-related masticatory muscle activity that has been associated with psychological stress, lifestyle behaviors, and various oral symptoms. However, evidence regarding these associations in the Thai population remains limited. This study investigated the associations between psychological stress, lifestyle behaviors, and morning symptoms in relation to frequent self-reported sleep bruxism among Thai participants. A cross-sectional online survey was conducted among 92 Thai participants using a structured questionnaire. Data were collected on demographic characteristics, sleep bruxism frequency, perceived psychological stress, bedtime lifestyle behaviors (including caffeine consumption, alcohol use, smoking, and bedtime), daytime tooth clenching, sleep-related respiratory conditions, and morning symptoms. Frequent sleep bruxism was defined as episodes occurring at least once per week. Associations were evaluated using Chi-square or Fisher’s exact tests, followed by multivariable logistic regression to examine adjusted associations. Model performance was assessed using receiver operating characteristic (ROC) analysis. the 92 participants, 28 (30.4%) reported frequent sleep bruxism. Daytime tooth clenching was significantly associated with frequent sleep bruxism in the univariable analysis (OR = 2.58, 95% CI: 1.03–6.41, p = 0.039), while morning jaw or facial pain showed the strongest association (OR = 7.54, 95% CI: 2.80–20.29, p < 0.001). Caffeine consumption before bedtime demonstrated a non-significant positive trend (OR = 2.17, 95% CI: 0.87–5.43, p = 0.094). After multivariable adjustment, no independent association remained statistically significant, although daytime tooth clenching showed the largest effect size (adjusted OR = 1.80, 95% CI: 0.92–3.54, p = 0.088). The multivariable model demonstrated modest discrimination (AUC = 0.678) with satisfactory calibration (Hosmer–Lemeshow p = 0.876). Frequent self-reported sleep bruxism was commonly reported in this study population and was associated with daytime tooth clenching and morning jaw or facial pain in univariable analyses. Although no independent factors were identified after adjustment, the findings support the multifactorial nature of sleep bruxism and highlight the importance of comprehensive behavioral and clinical assessment. Larger prospective studies using validated psychological instruments and objective diagnostic methods are warranted.